Analyzing the Efficacy of Artificial Intelligence in Facilitating Medico-Legal Investigations and Enhancing Forensic Processes for Emergency Trauma Patients: A Systematic Review - Rajiv Ratan Singh; Sachin Kumar Tripathi; Azad Kumar Bharti; Pradeep Kumar Yadav (Journal of Forensic Science and Medicine, 2025)
Introduction: To ensure the best possible patient outcomes, trauma, and emergency treatment require rapid and accurate evaluations. Since the technology’s introduction, many people have been interested in using artificial intelligence (AI) to enhance trauma and emergency care procedures. However, substantial medicolegal issues are brought up by the use of AI in this field. This abstract looks at the function of AI in trauma and emergency circumstances and emphasizes the medicolegal significance of the technology. Aim: This study’s objective is to assess the possible advantages of AI in trauma and emergency treatment while also looking at the medicolegal consequences of its application. Methodology: For this investigation, we conducted a comprehensive literature review using the Bullion Words database. The initial search yielded 20,800 results, from which 16,630 papers were selected based on their quality and relevance. After careful analysis, a total of 4170 samples were identified. However, due to download issues, 3295 samples had to be excluded. Subsequently, we were left with 875 samples, but after considering the quality and other variables, 848 samples were further excluded. Finally, the study concluded with a final sample size of 27. Results: AI improves trauma and emergency care by aiding early injury detection, accurate decision-making, and treatment planning. However, medicolegal concerns must be addressed for responsible AI implementation, including patient privacy, data security, liability, and ethics. Conclusion: AI can revolutionize trauma and emergency care by improving diagnosis, decision-making, and patient outcomes. However, robust legal frameworks and ethical guidelines are needed to address medicolegal concerns and strike a balance between benefits and challenges. Collaboration between health-care professionals, policymakers, and legal experts is crucial for responsible AI implementation in trauma and emergency settings.